Pengaruh Teknologi Pembelajaran terhadap Perkembangan Kognitif dan Kreativitas Siswa di Era Digital - Judijanto, Loso; Khoiri, M.; Arsyad, Muhammad; Sitopu, Joni Wilson; Sitepu, Ediaman (Westscience Press, 2024)
The integration of learning technology in education has transformed traditional teaching and learning practices, significantly influencing cognitive development and student creativity in the digital age. This study investigates the impact of learning technology on these two critical educational outcomes using a quantitative approach. Data were collected from 80 secondary school students through a structured questionnaire based on a Likert scale (1-5) and analyzed using SPSS version 26. The findings reveal a significant positive effect of learning technology on both cognitive development and creativity, with regression models explaining 46% and 52% of the variance, respectively. These results highlight the transformative role of digital tools in enhancing critical thinking, problem-solving, and creative expression among students. The study provides empirical evidence to guide educators and policymakers in designing effective strategies for technology integration in education.